KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN PESRTA DIDIK DI SDN 22 SULUR MEDAN TAHUN PELAJARAN 2023-2024 - Mawarni Mawarni; Topik, Hadisa Putri (Jurnal Komunikasi, 2025)
Principal leadership is the ablitity to mobilize existing resources in a school to be used optimally to achieve the expected goald. 1). The aim of this research is toreveal :What are the forms of school to improve students. 2). Implementing the program carried out by the school principal in improving students at sdn 22 Sulur Medan 2023-2024. 3) .Obstacles faced by school principals at SDN 22 Sulur Medan 2023-2024. This researcher used a phenomological type of research with a qualitative approach, data collection techniques using abservation interviews and documentation interviews and documentation while the data analysis techiniques used were data collection data reduction data presentation and drawing conclusions teachniques for cheking the validity of the data and using source collation and cheking. The results of this research show that : 1.       What are the forms of the principal's program in improving student discipline at SDN 22 Sulur Medan for the 2023-2024 academic year? There are several programs as follows: a. Rules obeyed by students and teachers. b. Regulations regarding class start times. c. Increase discipline towards students, so that if there are assignments at home (PR) they cannot be done at school, this is so that students can study at home when they are not at school. 2.       What is the implementation of the principal's program to improve student discipline at SDN 22 Sulur Medan for the 2023-2024 academic year. Preliminary activities in using the disciplinary learning process with students. Students who do not want to do assignments take a direct approach to students. The preliminary stage is already in the lesson plan. The obstacles faced by school principals in improving student discipline at SDN 22 Sulur Medan 2023-2024, there are 2 factors, namely internal consisting of within the students while external from outside, namely the social environment